IDENTIFICATION OF STAKEHOLDERS' ROLE IN THE SOCIAL ENTREPRENEUR OF SEA CULTIVATION OF VANAME SHRIMP (Litopenaeus vannamei) - Luthfa Jamilah; Mukhamad Najib; Kirbrandoko (Jurnal Manajemen & Agribisnis, 2019)
Mariculture of vaname shrimp, which is based on the social entrepreneur, is one of the strategies to improve the coastal welfare community. This concept focuses on enhancing the community's economy and environmental sustainability. To succeed in the business, an active role and stakeholder involvement is needed. This study aims to identify and map the role of stakeholders that influences business activities. Data analysis is carried out descriptively based on the results of identification, the typology classification, and the analysis of Dependence Mapping. The results of the study state that the role of stakeholders is divided into the internal and the external. The typology classification shows the educational institutions expect the role of definite owned by the group leader, the research and suppliers, the latent-discretionary by operational and marketing executives, the expected-dangerous by local governments, provincial governments and community leaders, the latent-dormant by the mass media and NGOs, the latent-discretionary by private companies, the latent demanding by financial institutions and MSMEs, and the expected-dependent by end consumers. The groups of stakeholders that influence the business are 1) High Interdependence consisting of group leaders, operational executors, finance and marketing, suppliers and private companies, and 2) Power Stakeholders consisting of end consumers, community leaders, local governments, educational and research institutions. Keywords: social entrepreneur, stakeholder, vaname, dependence mapping